Geant4‐DNA track‐structure simulations for gold nanoparticles: The importance of electron discrete models in nanometer volumes. Issue 5 (23rd March 2018) - Sakata, Dousatsu; Kyriakou, Ioanna; Okada, Shogo; Tran, Hoang N.; Lampe, Nathanael; Guatelli, Susanna; Bordage, Marie‐Claude; Ivanchenko, Vladimir; Murakami, Koichi; Sasaki, Takashi; Emfietzoglou, Dimitris; Incerti, Sebastien
Abstract : Purpose: Gold nanoparticles (GNPs) are known to enhance the absorbed dose in their vicinity following photon‐based irradiation. To investigate the therapeutic effectiveness of GNPs, previous Monte Carlo simulation studies have explored GNP dose enhancement using mostly condensed‐history models. However, in general, such models are suitable for macroscopic volumes and for electron energies above a few hundred electron volts. We have recently developed, for the Geant4‐DNA extension of the Geant4 Monte Carlo simulation toolkit, discrete physics models for electron transport in gold which include the description of the full atomic de‐excitation cascade. These models allow event‐by‐event simulation of electron tracks in gold down to 10 eV. The present work describes how such specialized physics models impact simulation‐based studies on GNP‐radioenhancement in a context of x‐ray radiotherapy. Methods: The new discrete physics models are compared to the Geant4 Penelope and Livermore condensed‐history models, which are being widely used for simulation‐based NP radioenhancement studies. An ad hoc Geant4 simulation application has been developed to calculate the absorbed dose in liquid water around a GNP and its radioenhancement, caused by secondary particles emitted from the GNP itself, when irradiated with a monoenergetic electron beam. The effect of the new physics models is also quantified in the calculation of secondary particle spectra, when originating in the GNP and when exiting from it. Results: The new physics models show similar backscattering coefficients with the existing Geant4 Livermore and Penelope models in large volumes for 100 keV incident electrons. However, in submicron sized volumes, only the discrete models describe the high backscattering that should still be present around GNPs at these length scales. Sizeable differences (mostly above a factor of 2) are also found in the radial distribution of absorbed dose and secondary particles between the new and the existing Geant4 models. The degree to which these differences are due to intrinsic limitations of the condensed‐history models or to differences in the underling scattering cross sections requires further investigation. Conclusions: Improved physics models for gold are necessary to better model the impact of GNPs in radiotherapy via Monte Carlo simulations. We implemented discrete electron transport models for gold in Geant4 that is applicable down to 10 eV including the modeling of the full de‐excitation cascade. It is demonstrated that the new model has a significant positive impact on particle transport simulations in gold volumes with submicron dimensions compared to the existing Livermore and Penelope condensed‐history models of Geant4.